The Role of School Counselors in Exploring Students' Interests and Talents Through Counseling and Skill Education - Pini Pitria; Mudjiran; Yeni Karneli (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this study is that school counselors can have an important role in identifying and exploring students' interests and talents. Through counseling and skill education, counselors can help students identify their talents and interests, and find ways to develop and explore their potential through skill education such as developing communication skills, teamwork, problem solving, and time management. Through skill education, counselors can help students develop these skills, so that they are ready to face challenges in the world of work and academics and through this approach, counselors can also help students reach their full potential, increase their involvement in school, and increase their chances of future success.